Whakaatuhia te hītori o te iwi o Marutuahu me ōna hāpū me nga taonga o te whenua, 1850 ki 1880 = Let the story be told : the iwi of Marutuahu and the discovery of gold, 1850 to 1880 : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Art in History at Massey University, Albany - Walsh, Judith Margaret-Mary (Massey University, 2006)
This thesis is a study of the interaction between Māori and Pākehā in the Hauraki region during the period 1850 to 1880. It examines the role played by the iwi of Marutuahu: Ngāti Maru, Ngāti Paoa, Ngāti Tamatera, and Ngāti Whanaunga in gold mining in the Hauraki region during this period. Three Hauraki goldfields, namely Coromandel, Thames and Ohinemuri, have been chosen as case studies to analysis the economic, political and social impact this involvement had on their lives. It offers a different perspective from what has been written previously about the participation of the tangata whenua of Hauraki in gold mining as it attempts to represent the discovery of gold from a Māori perspective. It looks at the role of the rangatira in distributing and utilizing the gold revenues, and examines at the tension that existed between their role in traditional Māori society and the impact of 'modernization'. It is argued that Māori involvement in these goldfields was primarily of an economic and entrepreneurial nature and it was due to circumstances beyond their control that they were unable to make a financial success of goldmining. This thesis concludes that the Hauraki rangatira who entered into the arrangements with the Crown to open their land for mining did so with the intention of improving the lifestyle of their people and to enable them to reap the benefits from participating in the colonial economy and that at no stage did these rangatira foresee the loss of their land and the damage that would occur to their traditional lifestyle.
Keywords: New Zealand; Hauraki District -- History; Thames-Coromandel District -- History; Auckland -- History; Maori (New Zealand people); Gold mines and mining; Māori Masters Thesis